PENGARUH STRATEGI PEMBELAJARAN MODULAR INSTRUCTION TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA KELAS VIII SMP N 3 MERANGIN - Miska Khoiriah (Pendidikan Matematika | STKIP YM Bangko, 2019)
The low ability of students' mathematical reasoning causes students difficulty solving mathematical reasoning ability questions on several indicators. The purpose of this study is to find out and describe the mathematical reasoning abilities taught with the Modular Instruction learning strategy better than those taught by conventional learning of Grade VIII students of SMP N 3 Merangin in the 2015/2016 Academic Year. This type of research is quantitative research that is experimental in design